Evaluation of the effect of sildenafil on nitric oxide secretion and improvement of endometrial receptivity in fresh ICSI cycles - Taher, Rabab Alwan; Kzar Al-Essami, Shereen Abdulhussien; Hussein Kadhim, Batool (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Endometrial receptivity is a chain of events that promotes embryo implantation and is regulated by a variety of substances, such as cytokines, growth factors, and steroid hormones. The study’s objective was to assess how vaginally delivered sildenafil in ICSI patients affects pregnancy outcome, endometrial thickness, subendometrial resistance index, and pulsatility index. Methods: The sixty women who participated in this controlled randomised trial (interventional experimental research) at the High Institute of Infertility Diagnosis and Assisted Reproductive Technologies underwent IVF/ICSI cycles. Patients were split into two groups: study group: from the day of the last menstrual period to the day of the hCG injection, thirty (30) infertile women got four (4) doses of vaginal sildenafil 25mg tablets daily. Thirty (30) infertile ladies who weren’t given sildenafil therapy made up the control group. Results: Nitric oxide levels in the study group’s serum were significantly significant. In the subendometrial Doppler research, the mean pulsatility index was considerably lower in the study group whereas the mean resistance index and mean systolic to diastolic ratio did not change statistically between the control and study groups. Between the control and study groups, there was no statistically significant difference in the mean endometrial thickness. The sildenafil group had a greater pregnancy rate, although the difference was not statistically significant. Conclusions: By enhancing subendometrial blood flow by lowering the pulsatility index and raising the nitric oxide (NO) factor, the use of vaginal sildenafil in a new ICSI cycle improves endometrial receptivity.